Flouting Maxim as a Trigger of Sarcasm and Humor: A Pragmatic Analysis of X Tweets by @TitaniaMcGrath - Evriliani Putri Darmawanti; Dewi Kustanti; Dian Budiarti (Universitas Pahlawan Tuanku Tambusai, 2026)
The research aims to analyze the flouting of conversational maxims in satirical tweets posted by Titania McGrath on X. Previous studies on maxim flouting have primarily focused on stand-up comedy, webtoons, and general online interactions, while the role of maxim flouting in ideological digital satire remains underexplored. To address this gap, this study investigates how conversational maxims are flouted in Titania McGrath’s tweets and how such flouting generates humor and sarcasm. Using a qualitative descriptive approach, the study analyzes selected tweets through Grice’s (1975) Cooperative Principle, implicature theory, humor theory, and cyberpragmatics. The findings reveal that the Maxim of Quality is flouted most frequently through hyperbole, implausible claims, and verbal irony, while the other maxims contribute to ambiguity, incongruity, and parody. This research contributes to pragmatic research by demonstrating how maxim flouting functions as a key mechanism of digital satire in social media discourse.